A tractable, simplified ex vivo human skin model of wound infection. Issue 4 (26th March 2019) - Yoon, Daniel J.; Fregoso, Daniel R.; Nguyen, Duc; Chen, Vivien; Strbo, Natasa; Fuentes, Jaime J.; Tomic‐Canic, Marjana; Crawford, Robert; Pastar, Irena; Isseroff, R. Rivkah
Abstract: The prevalence of infection in chronic wounds is well documented in the literature but not optimally studied due to the drawbacks of current methodologies. Here, we describe a tractable and simplified ex vivo human skin model of infection that addresses the critical drawbacks of high costs and limited translatability. Wounds were generated from excised abdominal skin from cosmetic procedures and cultured, inoculated with Staphylococcus aureus strain UAMS‐1, or under aseptic conditions. After three days, the infected wounds exhibited biofilm formation and significantly impaired reepithelialization compared to the control. Additionally, promigratory and proreparative genes were significantly downregulated, while proinflammatory genes were significantly upregulated, demonstrating molecular characterizations of impaired healing as in chronic wounds. This model allows for a simplified and versatile tool for the study of wound infection and subsequent development of novel therapies.